#TITLE_ALTERNATIVE# - PURWO SAPUTRO (NIM: 22014004), SUGENG
The region of this study is Tana Toraja and its surroundings where located at South Sulawesi province. Plutonic and volcanic rock at the study region contained high potassium based on geochemistry analysis compared to the other region. The cause and source of high potassium can be related to the process of magma formation under Tana Toraja. The data of this study consists of 46 data from petrograph analysis and 80 data from rock geochemistry (AA, AN, EA, ICP, and XRF). Some of the data was supported by absolute age from analysis using K-Ar method. High potassium matrix was found at absarokite, shoshonite, banakite, andesite, dacite, and rhyolite, with represented minerals such hornblende, biotite, K-feldspar, feldspathoid, and phlogopite. The magma source of study area was formed by two different sources, nearer to primitive mantel and also nearer to the surface. Rock texture, plagioclast composition, (Th/U) ratio and (K/Nb) ratio that valued > 2,50 and > 2100, and and some correlation between elements ratio indicated a contamination phenomenon and magma mixing. Magma at the study region is related to subduction process between ocean and continents (La/Yb > 7; Ba/Hf > 4).